Understanding and information failures in insurance: Evidence from India - Jean Philippe Platteau; Darwin Ugarte Ontiveros (Institute for Advanced Development Studies (INESAD), 2013)
This paper is an attempt to understand the factors behind low contract renewal rates frequently observed in insurance programs in poor countries. This is done on the basis of the experience of a microinsurance health program in India. We show that deficient information about the insurance product and the functioning of the scheme, and poor understanding of the insurance concept are the major causes of the low contract renewal rate among households which had previously enrolled into the program. A central finding is that, when a household has received a large negative payout during the preceding year, it is more inclined to opt out of the program unless it has a good understanding of what insurance means. In other words, the adverse impact of negative insurance payouts on contract renewal is conditional upon the presence of a cognitive bias which violates the expected utility theory. Moreover, trust in the insurance company has a significant positive effect, yet that effect cannot be disentangled from that of understanding ability. The policy implication of our findings is considerable since they provide a strong justification for mandatory universal health insurance.
Keywords: G21; I13; O12; 330; Microfinance; microinsurance; insurance literacy